Changes in number, morphology and volume of platelets during neonatal sepsis - M. Zakerihamidi; H. Boskabadi; M. Nayeri; Z. Badiee; F. Bagheri; S. Amirkhani (Инфекция и иммунитет)
Introduction. Thrombocytopenia is considered as one of the signs of sepsis but, Changes in number, morphology and volume of platelets is not widely researched upon in this matter. Therefore, the current study is aiming to analyze the changes in number, morphology and volume of platelets during neonatal sepsis. Materials and methods. This cross-sectional study has been carried out on 807 premature neonates suspected to have infection in Ghaem hospital Mashhad from 2015–2023 by using available sampling method. The data collection tool, researcher-made checklist included laboratory evaluations by which platelet indicators [Platelet count, Platelet distribution width (PDW) and mean platelet volume (MPV)] were measured and compared before, during infection and after recovery. Afterwards, platelet characteristics in septic neonates (Case group) were compared to neonates without definite signs of infection (Control group). Results. Two hundred ninety-five neonates (35.5%) had definitive sepsis. In the case group the number of platelets was less and the amount of MPV and PDW were higher than control group. The number of platelets decreases during infection, but this numbers increase after recovery. PDW increases during infection and after recovery. Fifty four percent of infected neonates had thrombocytopenia. Thrombocytopenia in 78% of neonates with sepsis caused by Klebsiella pneumoniae and in 58% of the cases caused Enterobacter aerogenes was seen. The optimal cutoff value of platelet to differentiate case from those of control group was lower than 100 000/mcL, with a sensitivity of 73%, specificity 12.2% (AUC = 0.427), MPV more than 9.8(fl), with a sensitivity of 80%, specificity 47% (AUC = 0.618), PDW more than 11.2(fl), with a sensitivity of 90%, specificity 28.4% (AUC = 0.763). Conclusion. During infection the number of platelets decreases, but MPV and PDW increase. Thrombocytopenia was seen more in gram-negative bacteria rather than gram-positive. During infection the number of platelets decreases but after recovery the number of platelets, MPV and PDW increases. Platelet indices have good sensitivity but low specificity in diagnosing definitive infection.